Increased serum S100B in elderly, chronic schizophrenic patients: negative correlation with deficit symptoms - Schmitt, Andrea; Bertsch, Thomas; Henning, Uwe; Tost, Heike; Klimke, Ansgar; Henn, Fritz A.; Falkai, Peter (Schizophrenia research, 2005)
In schizophrenia, elevations of serum and CSF S100B levels have been reported and related to state of the disease and negative symptoms. In elderly chronic schizophrenic inpatients with stable medication, S100B may be increased and correlated to psychopathology and neuropsychological deficits. We have measured serum levels of S100B in 41 elderly, chronic schizophrenic patients and 23 age- and gender-matched controls using an immunoluminometric assay. In patients, we assessed detailed psychopathology and neuropsychological performance and determined serum levels of haloperidol, clozapine and its two main metabolites desmethylclozapine and clozapine metabolite N-oxid by HPLC. S100B levels were increased in elderly chronic schizophrenic patients compared to healthy controls. In patients, levels were negatively correlated with deficit symptoms and positively with age. There were no significant differences of S100B between medication groups and no correlation with serum levels of antipsychotics or neuropsychological scores. Elevations of S100B in elderly chronic schizophrenic patients may be related to an active disease process lasting until old-age. Correlations point to the impact of S100B in neuroplasticity and ageing. Post-mortem studies should clarify the presence of altered S100B function in the brain and its relationship to neuroplastic or neurodegenerative processes.